#### Answer

(1, 3)

#### Work Step by Step

Multiply the second equation by 2
10x - 2y = 4
Add to the first equation
x + 2y = 7
10x - 2y = 4
11x = 11
x = 1
Plug x = 1 into x + 2y = 7
1 + 2y = 7
2y = 6
y = 3
Solution is (1, 3)

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(1, 3)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.